Universal Basic Income : Debate and Impact Assessment - Francese, Maura (IMF Working Papers; Working Paper, 2018)
This paper discusses the definition and modelling of a universal basic income (UBI). After clarifying the debate about what a UBI is and presenting the arguments in favor and against, an analytical approach for its assessment is proposed. The adoption of a UBI as a policy tool is discussed with regard to the policy objectives (shaped by social preferences) it is designed to achieve. Key design dimensions to be considered include: coverage, generosity of the program, overall progressivity of the policy, and its financing.